2021
DOI: 10.1029/2021gl094941
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Data Assimilation of Ocean Observations Into an Ocean‐Atmosphere Model

Abstract: A global climate model represents the physical processes of the ocean, sea ice, atmosphere, and land, as well as their interactions by coupling different components in one system. Within a climate model, the ocean and the atmosphere are the two main compartments, which are highly linked to each other. They give/receive their feedback to/from each other in one system thus influencing each other consistently. In contrast to stand-alone models of the ocean or atmosphere, which rely on forcings, a coupled model es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Here is a description of ESTKF (Tang et al, 2021). The state vector in the distributed hydrological assimilation model contains the grid values of soil moisture in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Here is a description of ESTKF (Tang et al, 2021). The state vector in the distributed hydrological assimilation model contains the grid values of soil moisture in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…They tested some configurations of DA and decided not to assimilate oceanic observations into atmosphere to avoid degrading the performance. Tang et al (2021) studied the influence of ocean observations in an atmosphere-ocean CDA system by assimilating sea surface temperature into an atmospheric model. To summarize, sCDA attracts researchers in various disciplines, and its application to various types of realistic coupled models has recently started.…”
Section: Research Articlementioning
confidence: 99%
“…Goodliff and Penny (2022) used a quasigeostrophic model and variational DA scheme and found that WCDA and SCDA perform similarly in the atmosphere, while WCDA leads to the lowest error in the ocean. Tang et al (2021) assimilated sea surface temperature observations into a global atmosphere-ocean model and found that WCDA and SCDA yield similar errors in the ocean. In the atmosphere, their results were state-variable and location dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Amidst the varied findings one thing is clear: the choice of coupled DA method depends on the model, model bias, observations, observation density, and underlying DA framework (e.g., ensemble or variational). Even within a single system the optimal method can vary spatially and by state variable (Tang et al., 2021; Yoshida & Kalnay, 2018). Given the value of coupled model initialization in subseasonal to seasonal forecasting and consistent reanalyses, it is important to investigate the potential benefits of SCDA and determine the conditions under which SCDA may outperform WCDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation